ADVANCES IN ALZHEIMER’S DISEASE TREATMENT - Bartosz Krawiec; Maja Ćwiek; Klaudia Malec; Amin Omidi; Bartłomiej Zarębski; Jakub Sójka; Maksymilian Szombara; Michał Mokrzyński; Piotr Szyszka; Olaf Jadanowski (International Journal of Innovative Technologies in Social Science, 2025)
Alzheimer’s disease (AD) remains one of the greatest challenges in modern medicine, serving as the leading cause of dementia in the elderly. Despite decades of research, effective causal treatment is still not available, and current therapies mainly focus on alleviating symptoms. However, in recent years, there has been significant progress in therapies targeting pathological proteins – amyloid β (Aβ) and tau – offering hope for modifying the course of the disease. In this review, we discuss the latest achievements in AD treatment, including clinical trial results involving monoclonal antibodies (lecanemab, donanemab), the role of biomarkers in early diagnosis, and the impact of non- pharmacological interventions such as diet and physical activity. Additionally, we analyze the challenges associated with anti-amyloid therapy, including side effects and limitations of current methods. We also emphasize the importance of personalized medicine and future research directions that may lead to breakthroughs in Alzheimer’s disease therapy. Materials and methods: This review was conducted systematically to identify and analyze relevant scientific literature regarding advancements in the treatment and diagnosis of Alzheimer’s disease. The PubMed database was searched. Articles were searched using the following words: "Anti-amyloid therapies"; "Alzheimer’s disease"; "Lekanemab"; "Donanemab"; "Alzheimer’s biomarkers"; "Cerebrospinal fluid"; "CSF"; "Tau protein"; "Non- pharmacological interventions"; "Mediterranean diet"; "Dementia prevention"; "Amyloid- related imaging abnormalities"; "Disease-modifying therapies”; „traumatic brain injury”.